EVALUATING THE AGENCY OF UNITED NATIONS FORUM ON FORESTS IN HALTING DEFORESTATION - Raharjo, Wahyu Arif; Fridiyanti, Yulita Nilam; Setiawan, Zudi (Spektrum, 2024)
The recent decrease in deforestation suggests a success in global effort of halting it, yet the question on in the agency of United Nations Forum on Forests (UNFF) remains. Do these changes occur due to UNFF’s facilitation? To examine this, this paper utilizes Principal-Agent theory proposed by Hawkins et al., (2006) to explore UNFF’s autonomy and discretion and its role in halting deforestation. It will first analyse the historical and relational foundation of UNFF as an international organization (IOs) and then define the meaning of ‘problem-solved’ in terms of forest issue. It will then evaluate policy instruments and powers that UNFF holds using Martha & Finnemore’s argument on the power of IOs. This paper argues that UNFF is serving as a forum for global forestry governance. It faces challenges due to differing national interests, limited discretion and significant role of NGOs in influencing discussions and advocating for sustainable forest management. Tensions persists between developed and developing nations in forestry issue, thus UNFF plays the role of collaboration and coordinating agents through Collaborative Partnership on Forest (CPF). It possesses limited role as arbitrating and enforcing agent due to Non-Legally Binding Instruments (NLBI) preferences of member states. However, UNFF possesses the power in terms of diffusing norms accepted by members, that halting deforestation is non-negotiable.